2018
DOI: 10.1055/s-0044-100612
|View full text |Cite
|
Sign up to set email alerts
|

Successful closure of a refractory rectal anastomotic fistula using endoscopic submucosal dissection combined with an over-the-scope clip

Abstract: Video 1 Endoscopic submucosal dissection of a patch of mucosa surrounding the fistulous orifice followed by over-the-scope clip (OTSC) closure.▶ Fig. 3 Endoscopic submucosal dissection of the mucosal area around fistulous orifice before clip closure. Endoscopic appearance: a of the fistulous orifice; b following submucosal injection; c after mucosal incision; d of the perifistulous mucosal defect after dissection and cold forceps avulsion. E100Barsic Neven et al. ESD with OTSC for refractory rectal anastomotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, it is still rarely used in the case of small leakages in rectal anastomosis after low anterior resection. Barsic et al [ 11 ] reported closure of an anastomotic leakage of the rectum in a single patient, however in this case an over-the-scope clip (OTSC,12/6 T; Ovesco, Tubingen, Germany) was utilized. Kadir et al [ 12 ] reported successful closure of an extraperitoneal rectal perforation with endoscopic hemoclips which occurred during transurethral urologic surgery.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…However, it is still rarely used in the case of small leakages in rectal anastomosis after low anterior resection. Barsic et al [ 11 ] reported closure of an anastomotic leakage of the rectum in a single patient, however in this case an over-the-scope clip (OTSC,12/6 T; Ovesco, Tubingen, Germany) was utilized. Kadir et al [ 12 ] reported successful closure of an extraperitoneal rectal perforation with endoscopic hemoclips which occurred during transurethral urologic surgery.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Nevertheless, large studies evaluating those methods are lacking and long-term resolution of chronic fistulas was obtained in less than 50% of cases [8,9]. Therefore, as previously proposed in case reports [10][11][12][13][14][15], we combined two approaches with both Endoscopic submucosal dissection (ESD) of the surrounding mucosa in order to promote healing combined with clip closure into the submucosal space to increase the chances of tight healing (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as previously proposed in case reports [10][11][12][13][14][15], we combined two techniques: endoscopic submucosal dissection (ESD) of the surrounding mucosa in order to promote healing, combined with clip closure into the submucosal space (FESDC) to increase the chances of tight healing (▶ Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Few cases of endoscopic treatment are currently reported with disappointing results [1]. Endoscopic submucosal dissection (ESD) of the fistula orifice combined with a clip closure has been described as effective for chronic oeso-tracheal [2,3] and rectal [4] fistulas after surgery or Crohn's disease [5]. We report here the first success of this technique, with video illustration (▶ Video 1), to treat a rectovesical fistula occurring after radical prostatectomy for adenocarcinoma.…”
mentioning
confidence: 97%